The teenagers’ idea about the prevention of crack - Juliana Macêdo Magalhães; Claudete Ferreira de Souza Monteiro; Maria do Livramento Fortes Figueiredo (Revista de Pesquisa Cuidado é Fundamental Online)
Objectives: To describe and understand ideas of adolescents on the crack use prevention. Methods: A qualitative study with the action research method was conducted, located at the Family Health Strategy, a community located in the state of Maranhao. The subjects were eleven adolescents. The data were collected by means of seminars and analyzed using content analysis. Results: It was observed that adolescents have the conception that the use of crack can be triggered by a lack of information. They feel the need to be more prepared in order to better understand the possible ways of prevention, complications and risks resulting from crack abuse. Conclusion: It is concluded that the professionals of the Family Health Strategy need to be more prepared when it comes to adolescents, so they can actually recognize the real needs of these individuals.